Electrical conductivity studies in polycrystalline (CuSe)1-xSex - Talib, Zainal Abidin; Liew, Josephine Ying Chyi; Zainal, Zulkarnain; Mat Yunus, Wan Mahmood; Lim, Kean Pah; Wan Yusoff, Wan Mohamad Daud; Abd. Moksin, Mohd Maarof (Universiti Putra Malaysia Press, 2009)
This studies are directed towards measuring the electrical conductivity of the (CuSe)1-xSex metal chalcogenide semi-conductor composites, with different stoichiometric compositions of Se (x = 0, 0.2, 0.4, 0.5, 0.6, 0.8,1.0) in bulk form. The electrical conductivity measurement was carried out at room temperature, using the parallel plate technique. The (CuSe) 1-xSex composites were prepared using solid state reaction, by varying the ratio of CuSe:Se, in the reaction mixture. The electrical conductivity of (CuSe) 1-xSex was determined to be in the range of 1.17 x 10-8 to 1.02 x 10-1 S/cm. The finding indicated that the electrical conductivity value tended to decrease as the concentration of Se increased. The effect of the concentration of Se, on electrical conductivity of (CuSe) 1-xSex composites, is discussed in this paper.